GEOTHERMIC STATUS OF THERMOPYLAE - ANTHILI AREA IN FTHIOTIDA PREFECTURE - Metaxas, A.; Varvarousis, G.; Karydakis, Gr.; Dotsika, E.; Papanikolaou, G. (Bulletin of the Geological Society of Greece, 2010)
The purpose of this study was the discovery, identification and evaluation of directly exploitable geothermal fields, in the Thermopylae - Anthili area (100km2 ). After the evaluation and the processing of any preexisting data, followed the surface works, such as further geological mapping, tectonic and stratigraphic correlations and analyses, geothermal impressions, observations at 30 recorded points (springs, drillings, wells) regarding water sampling, chemical analyses, temperature, pH and conductivity measurements, special sampling for Br and isotopes analyses. The in depth works that took place concern geophysical prospecting, loggings, small and large diameter drillings. All the data were digitized and processed in a GIS environment. After correlating all the data collected for the region, a geological - geothermal model was constructed. According to this model, water percolates through permeable formations, joints and faults, gets mixed with the existing salt water, warms up and then ascends to the surface through faults and concentrates on proper reservoirs. Specifically, the region of Damasta where two areas of hot water reservoirs have been identified is of particular geothermal interest. The first, located in Triassic– Jurassic limestones (more than 600m deep), presents the greatest interest in terms of temperature and capacity, while the second (found on the surface and up to 350m deep) is located in Quaternary sediments and the upper formations of the underlying Late Cretaceous limestone.